Secrets of the Sphinx - Giblin, James (Scholastic Press, 2004)
Discusses some of Egypt's most famous artifacts and monuments, including the pyramids, the Rosetta Stone, and, especially, the Great Sphinx, presenting research and speculation about their origins and their future.